2012
DOI: 10.1097/aci.0b013e32835923a6
|View full text |Cite
|
Sign up to set email alerts
|

History of primary immunodeficiency diseases

Abstract: This review illustrates the historic events that led to the discovery, classification, and molecular definition of PID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 12 publications
0
23
1
8
Order By: Relevance
“…In 1950, Eduard Glanzmann and Paul Riniker found that Candida albicans infections are associated with an absence of lymphocytes. 1 Two Swiss groups from Bern and Zurich (Hassig Cottier, R.Tobler and Walter Hitzig) discovered similar patients in 1958 and recognized it to be an immunodeficiency. This condition that was initially coined as Swiss type agammaglobulinemia was renamed as severe combined immunodeficiency (SCID) by world health organization (WHO) in 1970.…”
Section: Historymentioning
confidence: 99%
See 2 more Smart Citations
“…In 1950, Eduard Glanzmann and Paul Riniker found that Candida albicans infections are associated with an absence of lymphocytes. 1 Two Swiss groups from Bern and Zurich (Hassig Cottier, R.Tobler and Walter Hitzig) discovered similar patients in 1958 and recognized it to be an immunodeficiency. This condition that was initially coined as Swiss type agammaglobulinemia was renamed as severe combined immunodeficiency (SCID) by world health organization (WHO) in 1970.…”
Section: Historymentioning
confidence: 99%
“…This condition that was initially coined as Swiss type agammaglobulinemia was renamed as severe combined immunodeficiency (SCID) by world health organization (WHO) in 1970. 1 In 1954, Robert Good discovered a fatal granulomatous disease that is now known as chronic granulomatous disease (CGD). 1 Over the last 65 years, the field of PIDs has advanced exceedingly.…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Patients with primary immunodeficiency disorders are more likely to experience recurrent, serious, and unusual infections and have a tendency to develop a wide range of complications. [5][6][7] The true incidence and prevalence of primary immunodeficiency disorders are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Эра активного изучения ПИД началась в 50-60-е годы прошлого столетия, когда появился сам термин и были описаны первые варианты ПИД [6], расшиф-рованы некоторые механизмы их патогенеза [7], по-ложено начало заместительной терапии внутривен-ными иммуноглобулинами (ВВИГ) [8] и проведена первая трансплантация стволовых клеток [9].…”
unclassified